Microbial Stress Tolerance for Biofuels Systems Biology - Liu, Zonglin Lewis; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
The development of sustainable and renewable biofuels is attracting growing interest. It is vital to develop robust microbial strains for biocatalysts that are able to function under multiple stress conditions. This Microbiology Monograph provides an overview of methods for studying microbial stress tolerance for biofuels applications using a systems biology approach. Topics covered range from mechanisms to methodology for yeast and bacteria, including the genomics of yeast tolerance and detoxification; genetics and regulation of glycogen and trehalose metabolism; programmed cell death; high gravity fermentations; ethanol tolerance; improving biomass sugar utilization by engineered Saccharomyces; the genomics on tolerance of Zymomonas mobilis; microbial solvent tolerance; control of stress tolerance in bacterial host organisms; metabolomics for ethanologenic yeast; automated proteomics work cell systems for strain improvement; and unification of gene expression data for comparable analyses under stress conditions.
Genomics of yeast tolerance and in situ detoxification -- Genetics and regulation of glycogen and trehalose metabolism in Saccharomyces cerevisiae -- Molecular mechanisms of programmed cell death induced by acetic acid in Saccharomyces cerevisiae -- Molecular mechanisms of ethanol tolerance in Saccharomyces cerevisiae -- High gravity ethanol fermentations and yeast tolerance -- Improving biomass sugar utilization by engineered Saccharomyces cerevisiae -- Genomics on pretreatment inhibitor tolerance of Zymomonas mobilis -- Mechanisms and applications of microbial solvent tolerance -- Control of stress tolerance in bacterial host organisms for bioproduction of fuels -- Metabolomics for ethanologenic yeast -- Automated systems of plasmid-based functional proteomics to improve microbes for biofuel production -- Unification of gene expression data for comparable analyses under stress conditions.
Keywords: Life sciences; Biotechnology; Microbiology; Biological models; Cytology; Microbial genetics; Life Sciences; Microbial Genetics and Genomics; Systems Biology; Cell Biology; Biotechnology; Applied Microbiology